A Descriptive Study of the Quality of Life and Burden of Mothers of Children and Adolescents with Type 1 Diabetes. Issue 2 (3rd April 2023) - Gallegos, Erica; Harmon, Kasey B.; Lee, Gilliane; Qi, Yongyue; Jewell, Vanessa D.
Abstract: The purpose of this cross-sectional survey was to examine the quality of life and level of burden experienced by mothers of children and adolescents with type 1 diabetes (n = 199). Data was collected using a sociodemographic questionnaire, the Zarit Burden Interview Scale (ZBIS), and the World Health Organization Quality of Life-BREF (WHOQOL-BREF) instruments. A simple descriptive analysis was conducted, and the Pearson's correlation coefficient was utilized to determine the correlation among variables. Most respondents (68.9%) reported moderate to severe burden on the ZBIS. Across age groups, statistically significant, negative correlations were found between burden and physical health ( r = −0.371, p < 0.001), social relationships ( r = −0.389, p < 0.001), psychological health ( r = −0.445, p < 0.001) and environment ( r = −0.438, p < 0.001). Mothers of children and adolescents with type 1 diabetes reported an inverse relationship between burden and quality of life influenced by the occupation of caregiving. Occupational therapy practitioners can address strategies to reduce caregiver burden and improve mothers' quality of life.